Potentially inappropriate medications in elderly patients with heart failure: Beers Criteria-based study. (17th July 2020) - Zahwe, Mariam; Skouri, Hadi; Rachidi, Samar; Khoury, Maurice; Noureddine, Samar; Isma'eel, Hussain; Tamim, Hani; Al-Hajje, Amal
Abstract: Objectives: Primary objectives were to evaluate the use of potentially inappropriate medication (PIM) use in elderly heart failure (HF) patients and the factors associated with the number of PIMs. Secondary objectives were to test for the correlation between PIMs and quality of life (QOL) and depression. Methods: A cross-sectional study was conducted among 125 elderly Lebanese HF patients with left ventricular ejection fraction <50%. Data on socio-demographics, clinical data and medications were collected. Patients were interviewed with Minnesota living with Heart Failure Questionnaire (MLHFQ) and Patient Health Questionnaire-9 (PHQ-9). Medication profile per patient was evaluated for PIMs using Beers Criteria. The correlations between the number of PIMs and the MLHFQ, PHQ-9 and the number of medications were tested using Pearson's correlation. Linear regression was done to predict the factors associated with the number of PIMs. Key findings: Patients were taking a total of 1035 medications with a mean of 8.28 ± 3.14 medications. In total, 80.0% of patients were taking at least one PIM. Diuretics (55.2%) and proton pump inhibitors (41.6%) were most commonly prescribed PIMs. The number of PIMs was moderately correlated with the number of medications and the MLHFQ score. Linear regression showed that the number of medications, age ≥85 years, chronic kidney disease and HF with New York Heart Association III were associated with more PIMs. Conclusions: A high percentage of PIMs was found among a sample of elderly Lebanese HF patients. HF multidisciplinary team is needed to control the prescription of PIMs in this vulnerable population.